Mengintegrasikan Potensi Lokal Daerah dalam Matakuliah Telaah Kurikulum untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa Belajar Merdeka - Nurhidayati, Siti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
The purpose of this study is to describe how to integrate local potential in the Curriculum Study Course to improve students' critical thinking skills. This research is a qualitative descriptive study using research samples from students of the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education. The instrument used is a critical thinking ability test sheet in the form of 5 essay questions. The results of the analysis show that the critical thinking skills of stage I students reached 47.5% (critical enough), increased in stage II to 75% (critical), meaning that most of the students were critical in identifying various problems related to the curriculum and local learning resources, analyzing and reviewing the applicable curriculum, and selecting solutions and making decisions which are then used in learning in schools.